Distinct Neural Stem Cell Populations Give Rise to Disparate Brain Tumors in Response to N-MYC - Swartling, Fredrik J.; Savov, Vasil; Persson, Anders I.; Chen, Justin; Hackett, Christopher S.; Northcott, Paul A.; Grimmer, Matthew R.; Lau, Jasmine; Chesler, Louis; Perry, Arie; Phillips, Joanna J.; Taylor, Michael D.; et al. (Cancer cell, 2012)
The proto-oncogene MYCN is mis-expressed in various types of human brain tumors. To clarify how developmental and regional differences influence transformation, we transduced wild-type or mutationally stabilized murine N-mycT58A into neural stem cells (NSCs) from perinatal murine cerebellum, brain stem, and forebrain. Transplantation of N-mycWT NSCs was insufficient for tumor formation. N-mycT58A cerebellar and brain stem NSCs generated medulloblastoma/primitive neuroectodermal tumors, whereas forebrain NSCs developed diffuse glioma. Expression analyses distinguished tumors generated from these different regions, with tumors from embryonic versus postnatal cerebellar NSCs demonstrating Sonic Hedgehog (SHH) dependence and SHH independence, respectively. These differences were regulated in part by the transcription factor SOX9, activated in the SHH subclass of human medulloblastoma. Our results demonstrate context-dependent transformation of NSCs in response to a common oncogenic signal. [Display omitted] ► N-MYC contributes to both glioma and medulloblastoma ► N-MYC drives either SHH-dependent or -independent tumors, based on NSC age ► NSCs from different brain regions generate tumors with distinct signaling programs ► Transcription factor SOX9 is activated in SHH-dependent brain tumor cells